The Promulgation of Penal Provisions - Stewart, G (Victoria University of Wellington Law Review, 1997)
The following is an extract from a larger piece of research undertaken for the Law Commission’s Drafting Manual project, one aspect of which deals with the legislative drafting of penal provisions. Within that area, specific issues arose such as: Should an offence be created at all? What are the factual elements of the offence? What mental element is appropriate? What defences are to be available? How should the provisions be promulgated (e.g., in a statute? in regulations? in rules?)? This article addresses the problems raised by that last issue.